Analisis Proses Rekrutmen dan Seleksi pada PT Voksel Electric Tbk - Zikkra Ilham Malik; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2023)
Recruitment and Selection is one of the tasks of human resource management. Recruitment is the process of searching, finding and obtaining applicants to fill positions in a company. selection is the process of selecting a group of qualified candidates or individuals for available positions in a company. This research aims to analyze and describe the recruitment and selection process carried out at PT Voksel Electric Tbk, as well as evaluating its impact on labor recruitment and employee performance. The research method used is a qualitative descriptive approach by collecting primary data through observation, interviews and documentation, as well as secondary data from various trusted sources. The samples in this research were several employees of PT Voksel Electric Tbk. The sampling technique uses purposive sampling technique. From the results of this research, it can be seen that an optimal recruitment and selection process simultaneously contributes significantly to the company's competitive advantage. This research concludes that an effective recruitment and selection strategy will have a positive impact on company productivity, while implementation that does not meet the qualifications can have a negative impact on employee performance. The recruitment process is also proven to be the most dominant factor influencing employee performance, and therefore, special attention is needed to improve the recruitment process to ensure companies get employees who meet the company's needs and standards. Thus, this research provides important recommendations for companies to improve the recruitment and selection process in order to improve employee performance and strengthen the company's position in the market.